Incidence of chilli mite on chilli varieties under field conditions (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The current experiment was carried out to evaluate the occurrence of mites on chilli (Capsicum spp.) leaves. The trial was conducted in the experimental field and laboratory of RSRC, BARI, from December 2020 to April 2021. Three released varieties (viz. BARI Morich 1, BARI Morich 2, and BARI Morich 3) and six genotypes (Viz. G10, G13, G25, G27, G30, and G31) were used as the test crops of the experiment. The findings showed a considerable amount of variation among the treatments. Regarding the number of mites/leaf, the G25 had the highest mean number (7.24) whereas the G31 had the lowest (0.69). The G30 was the most productive in terms of yield (512.27 g/plant). The weight of each fruit and the number of fruits per plant were directly related to yield. On the contrary, the G10 and the G13 supplied an optimum yield per plant, whereas the G25 produced the least yield (21.02/plant). The correlation between yield and mite infestation was negative, and the results revealed that the BARI Morich-1, the G27, and the G31 were highly resistant to chilli mite infestation, and the G13, the BARI Morich-3, and the G30 were resistant, while the BARI Morich-2 was only moderately resistant. The G10 was tolerant and the G25 was susceptible to chilli mite infestation. The results concluded that the tested genotypes G13, G27, G30 and G31 showed remarkable resistance to mite infestation.J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 123-136, June-December 2022